Linear analysis of generalized turbulent hyperbolic flow in a rotating frame - Langer, Corey; Akylas, Evangelos; Kassinos, Stavros (My University, 2007)
We apply inviscid rapid distortion theory to the generalized case of turbulent hyperbolic flow in a rotating frame and investigate the dependence of the evolution of the turbulent kinetic energy on the frame rotation rate. We derive an analytical two-dimensional solution which allows for an accurate approximation of the three-dimensional initially isotropic problem. From the analytical solutions we determine a new generalized stability criterion for the evolution of the turbulent kinetic energy in this class of flows
Keywords: Aerodynamics; Turbulence; Isotropy subgroups; Fluid mechanics; Shear waves